Sociological analysis of the attitude to physical education of urban and rural schoolchildren in Сhina - Ponomarev V.V.; Bartnovskaya L.A.; Kravchenko V.M. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to conduct a sociological analysis of the attitude to the physical culture of urban and rural schoolchildren in China, identify patterns and trends and adopt positive pedagogical directions and design them into the domestic practice of physical education of schoolchildren. Methods and structure of the study. To conduct a sociological analysis of the attitude of Chinese schoolchildren to physical education, a questionnaire was developed. The survey was attended by urban and rural schoolchildren of the 7th-9th grades of the People's Republic of China. The total number of schoolchildren was 700 people (300 rural and 400 urban schoolchildren). Within the framework of mutual cooperation, graduate students studying at the Krasnoyarsk State Pedagogical University named after V.P. Astafiev conducted a survey of schoolchildren in China. Accordingly, the collected sociological material was processed and presented in the table. These results allow us to see a sociological picture of the attitude to the physical culture of urban and rural schoolchildren in China. Results and conclusions. A questionnaire of sociological analysis of attitudes towards the physical culture of urban and rural schoolchildren in China included nine main questions: What should be the teacher? Do you like creative teachers? What should be the main thing in the lesson of physical culture? Are your teachers strict? What does physical education teach you? Is it difficult for you to study in physical education lessons? What is not etched for you in physical education lessons? Et al. As the analysis of the survey results showed, the attitude of Chinese schoolchildren to physical education: more than 55% of Chinese schoolchildren love teachers with humor, who constantly contribute something new and interesting in their lessons; 80% of schoolchildren believe that the class needs to be differentiated by the level of physical fitness and 32% of children see the division of the class into girls and boys; 65% of schoolchildren in China do not like physical education, as they are very tired of physical activity. The sociological analysis made it possible to identify the strengths and weaknesses of teaching physical culture in Chinese schools and make appropriate adjustments to the practice of domestic physical culture in the country's schools.